Pengaruh Pemberian Edukasi melalui Multimedia Video Terhadap Kecemasan Pasien Pre Operasi Katarak Senilis di Instalasi Bedah Sentral RSPI Prof. Dr. Sulianti Saroso - Suara, Mahyar; Muamar, Muamar (Universitas Malahayati, 2025)
ABSTRACT Survey data from the Rapid Assessment of Avoidable Blindness (RAAB) estimates that 3 out of 100 people in Indonesia aged over 50 years are blind or around 1.6 million people. This data also states that 80% of them are caused by cataracts, placing Indonesia as the country with the highest rate of blindness in Southeast Asia. Various studies report that the prevalence of cataracts is generally caused by aging, namely aged 65-75 years, as much as 50%. This prevalence increases at ages over 75 years (Mo'otapu et al, 2015). In 2019, according to WHO, the latest global estimate is that 314 million people in the world will experience visual impairment and 45 million will experience blindness (Wiguna, 2018). Objective: to determine the effect of providing preoperative preparation education via multimedia videos on preoperative patient anxiety. senile cataract at the RSPI Central Surgical Installation Prof. Dr. Sulianti Saroso. Research Method: quantitative research research method with a quasi-experimental design and pretest post test control group. With the Paired T-test. Research Results: Based on the results of Bivariate Analysis with paired T-test with a sample size of 30 respondents (N=30), the data showed that T-Count (3.647) > T-table (0.418) and the p.Value (0.022) < alpha value ( 0.05) which means that the results of the normality test for the preoperative anxiety level of Senili Cataract Patients in this study showed significant Symp results, namely > 0.05, so the residual value was stated in This research has a Normal distribution. Conclusion: There is an influence between providing preoperative preparation education via multimedia video on patient anxiety before senile cataract surgery at the Central Surgery Installation of RSPI Prof. Dr. Sulianti Saroso in 2024. Keywords: Cataract, Education, Surgery, Video Media ABSTRAK Data survey Rapid Assessment of Avoidable Blindness (RAAB) diperkirakan 3 dari 100 orang di Indonesia berusia lebih dari 50 tahun mengalami kebutaan atau sekitar 1,6 juta orang. Data ini pula menyebutkan 80% diantaranya disebabkan oleh katarak, sehingga menempatkan Indonesia sebagai negara dengan angka kebutaan tertinggi di Asia Tenggara. Berbagai studi melaporkan jumlah prevalensi katarak penyebab umumnya akibat penuaan yaitu usia 65-75 tahun sebanyak 50%. Jumlah prevalensi ini meningkat pada usia di atas 75 tahun (Mo’otapu et al, 2015). Pada tahun 2019, menurut WHO dalam estimasi global terbaru yaitu 314 juta orang di dunia mengalami gangguan penglihatan dan 45 juta nya mengalami kebutaan (Wiguna, 2018). Untuk mengetahui pengaruh pemberian edukasi persiapan pre operasi melalui multimedia video terhadap kecemasan pasien pre operasi katarak senilis di Instalasi Bedah Sentral RSPI Prof. Dr. Sulianti Saroso. Metode peneliian penelitian kuantitatif dengan desain quasi eksperimen dan pretest post test control group. Dengan uji Paired T-test. Berdasarkan hasil Analisis Bivariat dengan paired T-test dengan jumlah sampel 30 responden (N=30) didapatkan data bahwa T-Hitung (3,647) > T-tabel (0,418) dan nilai p.Valuenya (0,022) < nilai alpha (0,05) yang berarti hasil uji normalitas tingkat kecemasan Pre Operasi Pasien Katarak Senili pada penelitian ini didapatkan hasil Signifikan Symp yaitu> 0,05 maka dinyatakn nilai residual dalam penelitian ini berdistribusi Normal. Ada pengaruh antara Pemberian Edukasi Persiapan Pre Operasi Melalui Multimedia Video Terhadap Kecemasan Pasien Pre Operasi Katarak Senilis Di Instalasi Bedah Sentral Rspi Prof. Dr. Sulianti Saroso tahun 2024. Kata Kunci: Katarak, Edukasi, Bedah, Media Video